THE DEVELOPMENT AND CHANGE OF THE ISLAMIC EDUCATION CURRICULUM IN INDONESIA(Historical, Sociological, Political, Economic and State Management Overview) - Kamaliah Kamaliah (Indonesian Journal of Education (INJOE), 2021)
Historically, the Islamic Education curriculum in which there is an Islamic Religious Education curriculum in Indonesia has developed and changed towards significant progress from the pre- independence era to the reform order. In a sociological view, the Islamic religious education curriculum functions to pass on the past culture to the next generation, so that the task of Islamic educational institutions is not only for the sake of social change, but also for the sake of awareness of the existence of Allah SWT as its goal. Politically, efforts to develop and change the curriculum cannot be separated from the influence of political changes that develop in the educational environment. Economically, an Islamic educational institution needs to develop a curriculum that is oriented to improving the quality and expertise of graduates of Islamic educational institutions so that they can be directly used in the job market. In the review of state management, local governments give autonomy to schools to formulate and design education policies which, although still seem centralized, educational institutions in the regions can still develop their curricula by incorporating local values and wisdom